2014
DOI: 10.1186/scrt489
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal stem cells, not conditioned medium, contribute to kidney repair after ischemia-reperfusion injury

Abstract: IntroductionStudies have shown that stem cells exert their therapeutic effects on acute kidney injury (AKI) through paracrine/endocrine actions. If the protective effect is mediated in an endocrine manner, the injection of the factors that these cells secrete could be effective, but the effect of conditioned medium (CM) remains controversial.MethodsIn this study, we cultured mesenchymal stem cells (MSCs) and then transplanted them into an ischemia-reperfusion (I/R) injury model. CM was also injected into mice,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
66
0
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(73 citation statements)
references
References 46 publications
(46 reference statements)
4
66
0
3
Order By: Relevance
“…In addition, significant increase in thickness of tubular basement membrane as compared with control group and significant decrease in PCNA immuno-reactivity as compared to stem cell-treated group was detected. Similar results were recorded by previous investigators [13] , who stated that even after administration of high consecutive doses of CM, no improvement had been observed in animal models of ischemia reperfusion kidney injury. On the contrary, other researchers reported that CM improved renal function and increased survival in AKI experimental models [37] .…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…In addition, significant increase in thickness of tubular basement membrane as compared with control group and significant decrease in PCNA immuno-reactivity as compared to stem cell-treated group was detected. Similar results were recorded by previous investigators [13] , who stated that even after administration of high consecutive doses of CM, no improvement had been observed in animal models of ischemia reperfusion kidney injury. On the contrary, other researchers reported that CM improved renal function and increased survival in AKI experimental models [37] .…”
Section: Discussionsupporting
confidence: 80%
“…One day after cisplatin injection, the BMSCs suspension was injected into the rat tail vein, in a dose of 2 x106 in 0.5 ml PBS/rat [13] . Rats of this group were sacrificed three days after cisplatin injection (4 th day of the experiment).…”
mentioning
confidence: 99%
“…The conditioned medium of OSR1 + SIX2 + cells was generated as previously reported [24]. In brief, 1 3 10 5 OSR1…”
Section: Graft Preparation and Implantationmentioning
confidence: 99%
“…In previous studies, MSC-conditioned medium and MSCs released by extracellular vesicles (Evs) were reported to exert renoprotective effects against AKI (9)(10)(11). The researchers attributed these effects to the favorable molecules, such as mRNA and miRNA (11) indicated that CM may not be able to protect against kidney injury (12,13). EVs, such as exosomes and shedding vesicles (also known as microvesicles; Mvs) are membranous structures that deliver bioactive molecular content, including proteins, mRNA and micro (mi)RNA sequences (14).…”
Section: Introductionmentioning
confidence: 99%